Activation of the neural pathway from the dorsolateral bed nucleus of the stria terminalis to the central amygdala induces anxiety‐like behaviors. (10th October 2018) - Yamauchi, Naoki; Takahashi, Daiki; Sugimura, Yae K.; Kato, Fusao; Amano, Taiju; Minami, Masabumi
Abstract: The bed nucleus of the stria terminalis (BNST) and the central amygdala (CeA) comprise a forebrain unit that has been described as the "extended amygdala". These two nuclei send dense projections to each other and have been implicated in the regulation of negative emotional states, including anxiety and fear. The present study employed an optogenetic technique to examine whether stimulation of CeA‐projecting dorsolateral BNST (dlBNST) neuron terminals would influence anxiety‐like behaviors in male Sprague‐Dawley rats. Photostimulation of CeA‐projecting dlBNST neuron terminals produced anxiogenic effects in an elevated plus maze test. This finding is inconsistent with previous reports showing that optogenetic stimulation of BNST neurons projecting to the lateral hypothalamus (LH) and ventral tegmental area (VTA) produces anxiolytic rather than anxiogenic effects. To address this issue, electrophysiological analyses were conducted to characterize dlBNST neurons projecting to the CeA, LH, and VTA. dlBNST neurons can be electrophysiologically classified into three distinct cell types (types I–III) according to their responses to depolarizing and hyperpolarizing current injections. Whole‐cell patch‐clamp recordings revealed that more than 60% of the CeA‐projecting dlBNST neurons were type II, whereas approximately 80% of the LH‐ and VTA‐projecting dlBNST neurons were type III. These electrophysiological results will help elucidate the mechanisms underlying the heterogeneity of BNST neurons during the regulation of anxiety‐like behaviors. Abstract : Stimulation of the neural pathway from the bed nucleus of the stria terminalis (BNST) to the central amygdala (CeA) produced anxiogenic effects, that is in contrast to the report that stimulation of lateral hypothalamus (LH)‐ and ventral tegmental area (VTA)‐projecting BNST neurons produces anxiolytic ones. Electrophysiological analyses demonstrated different proportions of cell types between CeA‐projecting (more than 60% are type II) and LH/VTA‐projecting (about 80% are type III) BNST neurons.